Joint Exposure to Ambient Air Pollutants Might Elevate the Risk of Small for Gestational Age (SGA) Infants in Wuhan: Evidence From a Cross-Sectional Study - Faxue Zhang; Xupeng Zhang; Yuanyuan Zhong; Shijie Zhu; Gaichan Zhao; Xiaowei Zhang; Tianzhou Li; Yan Zhang; Wei Zhu (Frontiers Media S.A., 2023)
Objective: To investigate the effect of exposure to multiple ambient air pollutants during pregnancy on the risk of children being born small for gestational age (SGA).Methods: An Air Pollution Score (APS) was constructed to assess the effects of being exposed to six air pollutants simultaneously, PM2.5, PM10, SO2, NO2, CO, and O3 (referred to as joint exposure). A logistic regression model was applied to estimate the associations of APS and SGA.Results: The adjusted odds ratios (ORs) of SGA per 10 ug/m3 increased in APS during the first and second trimesters and the entire pregnancy were 1.003 [95% confidence intervals (CIs): 1.000, 1.007], 1.018 (1.012, 1.025), and 1.020 (1.009, 1.031), respectively. The ORs of SGA for each 10 μg/m3 elevated in APS during the whole pregnancy were 1.025 (1.005, 1.046) for mothers aged over 35 years old vs. 1.018 (1.005, 1.031) for mothers aged under 35 years old. Women who were pregnant for the first time were more vulnerable to joint ambient air pollution.Conclusion: In summary, the results of the present study suggested that joint exposure to ambient air pollutants was associated with the increment in the risks of SGA.